Prevalence of Human Intestinal Parasitic Infections and Associated Risk Factors among School Children in Hakim District, Harari Regional State, Eastern Ethiopia - Eshetu Mekonnen; Nuredin Sadik (Advances in Public Health)
Background. The goal of this study was to determine the prevalence of intestinal parasitic infections and associated risk factors in the Hakim district of Harari Regional state, Eastern Ethiopia. This region is known for its high incidence of intestinal parasitic infections among socioeconomically disadvantaged communities in the tropics and subtropics. Materials and Methods. A cross-sectional study was carried out in a school setting from September 2021 to May 2022. The study involved 333 participants, including 158 males and 175 females, who were selected using a stratified systematic random sampling method. The stool samples were analyzed using both direct wet mount and formal ether concentration techniques, which were examined microscopically. A structured questionnaire was used to gather information on potential risk factors, and the data were analyzed using SPSS version 20. The P-value < 0.05 was considered statistically significant. Results. Out of 333 students screened, 96 (28.8%) tested positive for one or more intestinal parasites. The highest infection rate was recorded for G. lamblia at 28 (8.8%), followed by E. histolytica at 27 (8.1%). The overall prevalence of parasitic infections was 55 (16.5%). The lowest helminth infection rates were found for A. lumbricoides at 13 (3.9%), hookworm at 11 (3.3%), and T. trichiura at 10 (3%). The most significant risk factors associated with a high risk of Intestinal Parasitic Infections (IPIs) were sex, family size, latrine availability, defecation habit, frequency of hand washing, regular latrine cleaning habit, water source, and knowledge (P <0.05). However, there was no correlation between IPI prevalence and age, latrine type, or hand washing facility. Conclusion. Based on the research, it was found that IPIs are commonly seen among elementary school children in the Hakim district. To address this issue, it is recommended that the study area implement intensive healthcare interventions, trainings, and mass treatments for the treatment of IPIs.